Analisis Perbandingan Kinerja Keuangan dan Risiko Financial Distress Perusahaan Asuransi Umum Dual Listing Versus Single Listing di Indonesia (Lembaga Pengembangan Kinerja Dosen, 2025)
This article examines whether dual listing is associated with improved performance or reduced distress risk in general insurance companies in Indonesia. Using pooled firm–year data from 2022–2024 with 216 observations, the study compares Return on Assets (ROA) and Altman Z-Score between groups using the Mann–Whitney U test, and applies multiple linear regression with firm size (log of total assets) as a control. The results show no significant difference in the median ROA or Z-Score between dual-listed and single-listed companies. In the regression analysis, listing status is not associated with either ROA or Z-Score, while firm size is positively and significantly related to ROA. These findings indicate that profitability is more influenced by business scale than by listing status. The very low explanatory power for the Z-Score suggests that distress risk is more determined by prudential and operational factors not included in the model. Practically, dual listing alone does not guarantee higher profitability or lower distress risk; managerial focus should be directed toward underwriting quality, cost efficiency, and capital strength, while regulators strengthen prudential supervision and disclosure transparency.